(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2015)
Choosing a profession is complex and often affects many areas of one’s future life. In a representative study we analyzed data of 4,447 German adolescents, aged seventeen, who were interviewed in the years between 2000 and 2013. The aim of the study was to identify the effects of gender, school type, personality and leisure activities on vocational expectations and career-choice stages of generation Y. Especially, it was of interest which effect remained as a generational time effect after controlling for the named variables. For the analysis we used descriptive statistics with rank orders and mean values as well as linear and logistic regression analyses. Engagement in different leisure activities, gender and form of education all greatly affect the perceived importance of profession characteristics. While young women and students from German grammar schools rank “stimulating tasks” first, young men and students from all other school forms feel that a “secure position” is the most important. Also, personality factors influence the perceived importance of vocational features, with agreeable and extravert adolescents rating “contact to others”, “importance to society”, “helping others” and similar features significantly higher. After controlling for the named variables, there remained a significant correlation between the survey year and the term “secure position” which became less important, and the terms “working conditions”, “importance for society” and “helping others” all three of which became more important. A trend towards a higher valuation of one’s individual social responsibility can thus be noticed. Keywords: Professional choice, expectations, adolescents, generation Y